What are the main themes to conceptualize a nice reading technological support for children? - Damil, F.; Rodrigues, L.; Oliveira, A. (11th annual International Conference of Education, Research and Innovation, CERI2018, 2018)
In this world of information and knowledged, where everything seem connected, there is a notable and growing interest of children in relation to technologies, conveying information in a fast, dynamic and visual way, often incorporating videos, gifs, sounds or images. Contents are often neglected, in concise messages. On the contrary, a book requires time and attention from the reader. Consequently it increases the disinterest by reading books and the meeting with consecrated authors. The present study born from this problematic, in order to verify what should be the key concepts to consider in the development of a technological application (app) to reading support, particularly in the case of children. Through interviews with educational professionals we obtained the data to elaborate a concept map – using Leximancer –, in which we found three main themes (Consultation, Curiosity and Reading), representing the most important concepts in the proposal and development of the intended app. Motivation for reading should always be a main issue, being essential that children be attracted by the curiosity to consult texts through a technological support. This paper proposes the key concepts, or requirements, that must be taken into account in the development of a new technological prototype for reading support, toward children.